CCTV, Risk Management and Regulation Mechanisms in Publicly-Used Places: a Discussion Based on Swiss Examples - Ruegg, Jean; November, Valérie; Klauser, Francisco (My University, 2004)
This paper focuses on the relations between different actors involved in conceiving and using video-surveillance systems. More specifically, it deals with the reasons that support the growing use of CCTV, and the organisation structures and implementation schemes that are designed to cope with them. Based on four Swiss case studies, the analysis raises issues linked to the complexity of social and spatial relations that CCTV tends to produce.